Locally Enhanced Flow and Electric Fields Through a Tip Effect for Efficient Flow-Electrode Capacitive Deionization - Ziquan Wang; Xiangfeng Chen; Yuan Zhang; Jie Ma; Zhiqun Lin; Amor Abdelkader; Maria-Magdalena Titirici; Libo Deng (Nano-Micro Letters)
Highlights Steel tip arrays were used as current collectors to replace planar conductors. Optimal flow and electric fields reduced barriers for electron and ion transport. Desalination performance of flow-electrode capacitive deionization is enhanced by the tip-array current collectors.